The Analysis of Implementing Environmental Accounting on Waste Management (PG Djatiroto) - Fitri Nilasari (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The implementing environmental accounting on waste management at PG Djatiroto aims to analyze components of environmental costs (on waste management) and to analyze an accounting treatment of the environmental costs on waste management. The data analysis method used in this study is a comparative descriptive analysis method. The data in this study was obtained through interviews and documentation related research issues. Analysis done by comparing the results of interviews and document analysis by Hansen and Mowen theory for the environmental costs of components and SFAS 11 paragraph 1, SFAS 14, and SFAS No. 1 revision 2009 for the treatment accounting of environmental cost. Based on the results of this research is that the company has made the classification of environmental costs (in terms of waste management) and has conducted environmental cost accounting treatment stages. However, based on the analysist has been done, there are a few suggestions to be considered for the PG Djatiroto in term implementing environmental accounting for the future